Exploring the Complexity of the Book of Daniel: A Multifaceted Analysis - Venantius, Supriyono; da Silva, Denes Fernando Costa (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2024)
This research delves into the intricate layers of the Book of Daniel, seeking to unravel its complexities through a comprehensive examination. Emphasizing the historical and literary significance of the text, the study explores the multifaceted nature of the Book of Daniel, which has intrigued scholars for centuries. The primary objective is to illuminate various dimensions of complexity, including symbolic language, prophetic elements, and historical context. Employing a methodological approach that integrates literary analysis, historical investigation, and theological perspectives, the study aims to provide a holistic understanding of the Book of Daniel's intricacies. Positioned within ongoing scholarly discussions on biblical interpretation and prophecy, the research reveals that the Book of Daniel invites diverse approaches, incorporating historical, wisdom, prophetic, and apocalyptic perspectives. Comprehending the Book of Daniel's complexity contributes to bridging the gap between historical, literary, and theological viewpoints, thereby enriching our grasp of biblical texts and fostering scholarly discourse in this field.